GIS in urban planning and management: Malaysian experience - Yaakup, Ahris; Muhamad Ludin, Ahmad Nazri; Sulaiman, Susilawati; Bajuri, Haibenarisal (2005)
Since the seventies, Malaysia is experiencing a rapid urbanization rate and becoming one of most developed countries in the Asia region. Urbanization contributes many advantages in terms of economics, but if uncontrolled, would produce negative consequences to the physical, social and natural environment. With the advancement of Geo-information Technology (GIT), which considerably influenced the dynamic nature of urban and regional planning, incorporation of GIT becomes imperative for better and improved decision-making in urban planning and management. It offers a solution to the urban problems and decision-making, which is more reliant to the real-time spatial modeling. Based on the Town and Country Planning Act 1976 (Act 172) latest amended in 2001, the development plans provide the development framework and guidelines which need to be continually updated according to the present situation of development. The integration of Geographical Information System (GIS) has provided a tool which can contribute to much clearer understanding of real planning problems as well as prescriptive planning scenarios to enhance the quality of urban planning and management. This paper will enlighten the need for GIS at strategic planning and management level. Example of the use of GIS for strategic planning at the higher level relates to the National Physical Plan, Regional Plan and State Structure Plan whereas at local planning level, the integration of GIS is at District Local Plan and Area Action Plan. This paper will also highlight on how GIS is applied for urban management purposes with focus on development control. GIS notably provide a strong platform to decision maker in its role as the main component in Planning Support System (PSS) and Decision Support System (DSS). Some discussion on database design, the analysis techniques, the framework of planning and management incorporating GIS will end the paper.